Epipsammic Diatom Cocconesis sp. as New Bioeroder in Scleractinian Coral - Oktiyas Muzaky Luthfi; Adhimas Haryo Priyambodo; Muliawati Handayani; Yenny Risjani; Andrzej Witkowski (Faculty of Fisheries and Marine Universitas Airlangga, 2023)
Highlight Research The endolithic bioeroders were identified. Cocconeis sp. was new for the science of euendolithic bioeroder of Scleractinian coral. SEM revealed Cocconeis sp. etch and bore of coral skeleton. Pennate diatom was present on coral cavities. Abstract Laminar coral, Montipora, contributes to the coral reef ecosystem. The laminar life form is usually used by juvenile reef biota to shelter and prey. In an intertidal area, such as Pantai Kondang Merak, these corals are susceptible to erosion caused by mechanical and biological forces. Strong current or other anthropogenic activity may break coral colonies into pieces. Also, some grazers from reef fish and bioeroder potentially weaken coral structures. This study aimed to find the effect of biological agents from Bacillariophyceae, such as Cocconeis diatom, on the bioerosion process in laminar coral, e.g., Montipora. Ten montiporid corals from Pantai Kondang Merak were observed to find bio-eroding activities. Each coral colony was divided into 12 parts and photographed to record signs of bio-erosion on coral surface. While observing microborers, a 2x2 cm of the coral surface was observed using Scanning Electron Microscopy (SEM). SEM revealed that a frustule of Cocconeis sp. was found inside aragonite laminar coral from Pantai Kondang Merak. Cocconeis naturally grows on the coasts of tropical oceans as benthic organisms. They are reported as living attached to many substrates' surfaces and within the substrate as euendolith. This study revealed that Cocconeis sp. lived inside the coral skeleton as micro bioeroder by attaching their valve in coral aragonite. Further work needs more observations of another potential euendolith diatom living inside the coral and to build new information on their mechanism of bio-eroding process in more detail.